Use of Circulating and Cellular miRNAs Expression in Forensic Sciences - Dumache Raluca; Rogobete Alexandru Florin; Sandesc Dorel; Bedreag Ovidiu Horea; Ciocan Veronica; Muresan Camelia; Stan Adrian Tudor; Sandesc Mihai; Dinu Anca; Popovici Sonia Elena; Enache Alexandra (Journal of Interdisciplinary Medicine, 2017)
The current practice in the field of forensic medicine imposes the use of modern investigation techniques. The complexity of laboratory investigation methods needed for a final result of the investigation in forensic medicine needed new biomarkers of higher specificity and selectivity. Such biomarkers are the microRNAs (miRNAs), short, non-coding RNAs composed of 19–24 nucleotides. Their characteristics, such as high stability, selectivity, and specificity for biological fluids, differ from tissue to tissue and for certain pathologies, turning them into the ideal candidate for laboratory techniques used in forensic medicine. In this paper, we wish to highlight the biochemical properties and the usefulness of miRNAs in forensic medicine.